Impulsivity and Difficulties in Emotional Regulation as Predictors of Binge-Watching Behaviours - Starosta, Jolanta; Izydorczyk, Bernadetta; Sitnik-Warchulska, Katarzyna; Lizińczyk, Sebastian (Frontiers in Psychiatry, 2021)
Recently, the question about the potentially problematic characteristics of binge-watching behaviours has been raised in the contemporary literature. Binge-watching is a highly popular behaviour that involves watching multiple episodes of TV series in one sitting. Studies show that binge-watching can be both an entertaining, but also a potentially problematic, behaviour. Therefore, this research aimed to answer the question about how impulsivity, difficulties in emotional regulation, and one's motivations around why they want to watch a TV series predict problematic binge-watching among a group of Polish young adults. The research group consisted of 645 participants. The following tools were then used to measure the study variables: the Impulsive Behaviour Scale, the Difficulties in Emotion Regulation Scale, the Viewing Motivation Scale, and the Questionnaire of Excessive Binge-watching. Furthermore, a regression analysis was performed on the responses to each measure in order to answer our research questions. Our results show that a lack of premeditation, impulse control difficulties, and having an escapist motivation are all significant predictors of problematic binge-watching behaviours. Furthermore, one's motivations around dealing with loneliness, their motivations around how to best spend their free time, as well as their informative and entertaining motivations were also found to be significant predictors of problematic binge-watching behaviours.